"Floating Hip" and "Floating Knee" Associated with Hip Dislocation, Sciatic Nerve Palsy, and Patella Fracture: A Case Report. Issue 1 (January 2022) - Saini, Mukesh Kumar
Abstract : Case: We report a very rare case of simultaneous ipsilateral floating hip and floating knee (SIFHFK) injury with the neck of the femur and patella fracture and hip dislocation associated with sciatic nerve injury in a 45-year-old man after a road traffic accident. We adopted a staged approach for surgical fixation of the fractures after stabilization. At the latest 2 years follow-up, the patient was asymptomatic with satisfactory clinical outcome. Conclusion: SIFHFK injuries present a challenging and emergent clinical scenario and require extensive clinical experience, careful planning, and multidisciplinary teamwork because of the paucity of specific treatment protocols for the treatment of this complex injury.